Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Seed removal in two coexisting oak species: ecological consequences of seed size, plant cover and seed-drop timing - Pérez-Ramos, Ignacio M; Urbieta, Itziar R; Marañón, Teodoro; Zavala, M A; Kobe, Richard K (Oikos, 2008)
Seed predation and dispersal can critically influence plant community structure and dynamics. Inter-specific differences arising at these early stages play a crucial role on tree recruitment patterns, which in turn could influence forest dynamics and species segregation in heterogeneous environments such as Mediterranean forests. We investigated removal rates from acorns set onto the ground in two coexisting Mediterranean oak species –Quercus canariensis and Q. suber– in southern Spain. We developed maximum likelihood estimators to investigate the main factors controlling probabilities of seed removal and to describe species-specific functional responses. To account for inter-specific differences in seed-drop timing, two experiments were established: a simultaneous exposure of acorns of the two species (synchronous experiments) and a seed exposure following their natural seed-drop phenology (diachronic experiments). A total of 1536 acorns were experimentally distributed along a wide and natural gradient of plant cover, and removal was periodically monitored for three months at two consecutive years (with contrasting differences in seed production and thus seed availability on the ground). The probability of seed removal increased with plant cover (leaf area index, LAI) for the two oak species. Inter-specific differences in acorn removal were higher in open areas and disappeared in closed microhabitats, especially during a non-mast year. Despite later seed-drop, Q. suber acorns were removed faster and at a higher proportion than those of Q. canariensis. The higher probability of seed removal for this species could be attributed to its larger seed size compared to Q. canariensis, as inter-specific differences were less pronounced when similar sized acorns were exposed. Inter-specific differences in seed removal, arising from seed size variability and microsite heterogeneity, could be of paramount importance in oak species niche separation, driving stand dynamics and composition along environmental gradients.
Keywords: plant cover (voyant); Quercus canariensis; Quercus suber; Seed removal; Seed size

Soil water content and emergence time control seedling establishment in three co-occurring Mediterranean oak species - Urbieta, Itziar R; Pérez-Ramos, Ignacio M; Zavala, MIGUEL a; Marañón, Teodoro; Kobe, Richard K (Canadian Journal of Forest Research, 2008)
Tree species can differ in their responses to resource availability during the critical phase of establishment, which could influence forest dynamics. In Mediterranean forests, most of the attention has focused on the effects of shade and summer drought on seedling survival, but little is known about the effect of autumn to spring rains on earlier stages of recruitment. A sowing experiment was set up along natural light and water gradients with three co-occurring oak species (Quercus suber L. (cork oak), Quercus canariensis Willd. (Algerian oak), and Quercus pyrenaica Willd. (Pyrenean oak)) that show limited natural regeneration in southern Spain. Recruitment stages were monitored for 1 year. Models of seed germination, seedling emergence, and seedling survival as well as of overall recruitment patterns were developed as functions of light, soil moisture, and soil compaction. The influence of intraspecific variation in seed mass and emergence time were also tested. Excess soil water levels during the winter reduced germination and emergence and lengthened time to emergence (in waterlogged open areas), which in turn decreased seedling survival during the dry season. Seedlings from larger seeds were more likely to germinate and emerge. The results suggest that temporal and spatial variability of soil water content, mediated by emergence time and seed size, play a crucial role in the regeneration dynamics of Mediterranean oak forests.
doi: 10.1139/X08-089
Keywords: Mediterranean oak species; Modelling; seed germination; seedling emergence; seedling survival (voyant); Soil water content